Antioxidant potential of two Apiaceae plant extracts: a comparative study focused on the phenolic composition - Martins, Natália (2016)
The present study aimed to characterize the extracts prepared from Pimpinella anisum L. (anise) and Coriandrum sativum L. (coriander) (Apiaceae plants) seeds in terms of phenolic composition, and to correlate the obtained profiles with the antioxidant activity. Anise gave the highest abundance in phenolic compounds (42.09± 0.11 mg/g extract), mainly flavonoids (28.08±0.17 mg/g extract) and phenolic acids (14.01±0.06 mg/g extract), and also the highest antioxidant potential, accessed for the ability to inhibit lipid peroxidation and -carotene bleaching, reducing power and free radical scavenger activity. Apigenin and luteolin derivatives, as also caffeoylquinic acid derivatives appear to be directly related with the higher in vitro antioxidant potential of the anise extract.. In contrast, the weak antioxidant potential of coriander seems to be due to their lower abundance in phenolic compounds (2.24±0.01 mg/g extract). Further studies are necessary to evaluate the in vivo antioxidant potential of the tested extracts, but the performed in vitro experiments highlight them as potential health promoters.